Statistical issues in searches for new phenomena in High Energy Physics. (23rd January 2018) - Lyons, Louis; Wardle, Nicholas
Abstract: Many analyses of data in High Energy Physics are concerned with searches for New Physics. We review the statistical issues that arise in such searches, and then illustrate these using the specific example of the recent successful search for the Higgs boson, produced in collisions between high energy protons at CERN's Large Hadron Collider.